2020
DOI: 10.1177/2056305120942886
|View full text |Cite
|
Sign up to set email alerts
|

What Is WhatsApp for? Developing Transmedia Skills and Informal Learning Strategies Through the Use of WhatsApp—A Case Study With Teenagers From Spain

Abstract: Smartphones and WhatsApp are, respectively, the medium and application that Spanish teenagers most want. However, research into the use of WhatsApp is still quantitatively and qualitatively limited. In addition, little research has been carried out regarding its impact on the development of transmedia skills and informal learning strategies outside the classroom. This article aims to expand the knowledge on teenagers’ motivations and their development of transmedia skills and informal learning strategies in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…It because there will be many misunderstandings in conveying material relating to story-based questions (exploration) and it can be resolved by communication occurs smoothly. The use of the WhatsApp group application is also able to improve interpersonal skills between students (Sánchez & Pico, 2020) When students have difficulty solving questions in the form of stories question (exploration), the teacher can provide appropriate direction in the form of sample questions, case examples or directions in the stages of solving these questions.…”
Section: Discussionmentioning
confidence: 99%
“…It because there will be many misunderstandings in conveying material relating to story-based questions (exploration) and it can be resolved by communication occurs smoothly. The use of the WhatsApp group application is also able to improve interpersonal skills between students (Sánchez & Pico, 2020) When students have difficulty solving questions in the form of stories question (exploration), the teacher can provide appropriate direction in the form of sample questions, case examples or directions in the stages of solving these questions.…”
Section: Discussionmentioning
confidence: 99%
“…ere are several theoretical studies to demonstrate the potential of WhatsApp in education, mainly through group chat, collaborative activities, calls, and video calls [11]. Empirical studies allow asserting that its educational use allowed improving digital skills and engagement in students [11][12][13].…”
Section: 3mentioning
confidence: 99%
“…Furthermore, other types of disorders are found in some studies. For example, Costa-Sánchez and Guerrero-Pico (2020), Longstreet and Brooks (2017) and Sha et al (2019) found clear causal associations between life satisfaction and SNS addiction (e.g. WhatsApp) and Internet addiction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers in psychology and other fields sound alarm bells on the rising issues that surround the problematic use of the Internet (PIU) and Internet addiction (IAD) (Chen, 2020; Costa-Sánchez and Guerrero-Pico, 2020; Anderson et al , 2017; Cheever et al , 2018; Griffiths et al , 1999; Laconi et al , 2017; Longstreet and Brooks, 2017; Longstreet et al , 2018; Tao et al , 2010; Young, 2004; Zhang et al , 2008; Zhou et al , 2018). This is not a phenomenon that only clinical scholars pay attention to but also social and behavioural scientists believe that such problems indeed exist at dramatic levels due to the advancements in technology in recent years (Chou et al , 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation